Multicenter (FX)n/NH3 Halogen Bonds (X = Cl, Br and n = 1-5). QTAIM Descriptors of the Strength of the X∙∙∙N Interaction - Buralli, Gabriel Jesús (2017)
In the present work an in depth deep electronic study of multicenter XBs (FX)n/NH3 (X = Cl, Br and n = 1–5) is conducted. The ways in which X∙∙∙X lateral contacts affect the electrostatic or covalent nature of the X∙∙∙N interactions are explored at the CCSD(T)/aug-cc-pVTZ level and in the framework of the quantum theory of atoms in molecules (QTAIM). Calculations show that relatively strong XBs have been found with interaction energies lying between −41 and −90 kJ mol−1 for chlorine complexes, and between −56 and −113 kJ mol−1 for bromine complexes. QTAIM parameters reveal that in these complexes: (i) local (kinetics and potential) energy densities measure the ability that the system has to concentrate electron charge density at the intermolecular X∙∙∙N region; (ii) the delocalization indices [δ(A,B)] and the exchange contribution [VEX(X,N)] of the interacting quantum atoms (IQA) scheme, could constitute a quantitative measure of the covalence of these molecular interactions; (iii) both classical electrostatic and quantum exchange show high values, indicating that strong ionic and covalent contributions are not mutually exclusive.